Nataraja and the goddesses on the doorframe of the Sadashiva Temple - Temples of India Project Team (Jio Institute, 2024)
The lintels above the shakhas (vertical bands) of the Sadashiva Temple depict a dancing Shiva at the centre accompanied by a musician and a dancer. Goddesses are shown on the extreme ends. Shiva is portrayed as ten-armed, holding an akshamala (rosary), khatvanga (staff with a skull), damaru (drum), snake, kapala (skull), and trishula (trident), with his front two arms making dance a gesture. The goddesses are depicted as four-armed, wearing a jatamukuta (a crown of matted hair). They hold an akshamala and kamandalu (water pot), while their other hands hold their respective attributes.